Securities financing and asset markets: New evidence - Tomas Breach; Thomas B. King (Federal Reserve Bank of Chicago, 2018)
This paper presents new evidence on bilateral securities financing based on the Federal Reserve's Senior Credit Officer Opinion Survey, which was launched in the wake of the financial crisis to provide a window into this otherwise opaque market. The survey asks large broker-dealers about terms at which they fund client positions, and the demand for such funding, across several different collateral types. Within asset classes, reported changes in spreads, haircuts, and other financing terms move closely together, and we show that they also covary with the state of the underlying cash securities markets. Funding conditions are particularly highly correlated with measures of cash-market liquidity, and, by exploiting dealers' self-reported reasons for changing terms, we show that most of this correlation results from dealers responding to liquidity, rather than the other way around. Controlling for securities-market conditions, haircuts and spreads are unresponsive to shifts in funding demand; however, they do tend to tighten when measures of dealer condition deteriorate.
Keywords: 330